Normal Vestibulo-Ocular Reflex (VOR) gain measured using Video Head Impulse Test (vHIT) in healthly young adults, - Jamaluddin, Saiful Adli; Omar, Nor Amira (2019)
Introduction: Many new objective tests to assess the function of specific structures of the vestibular organ are currently adopted in vestibular clinics. One of the objective assessments include the video head impulse test (vHIT) where gain & velocity responses of eye relative to the head movements are recorded using an infrared camera. Methods: Thirty normal hearing subjects age between 18 to 25 years old participated in this study. At least ten Lateral, Left Anterior Right Posterior (LARP), and Right Anterior Left Posterior (RALP) responses were recorded for each participant by making small and rapid unpredictable head movements. Results: The average velocity gain for Lateral responses at 40 ms, 60 ms and 80 ms were 1.05 ± 0.003, 1.03 ± 0.002 and 1.01 ± 0.003 respectively. The LARP average velocity regression were 1.01 ± 0.24 for Left Anterior and 1.05 ± 0.25 for Right Posterior, with an average gain asymmetry of 5.13%. The RALP average velocity regression were 1.08 ± 0.31 for Right Anterior and 1.12 ± 0.30 for Left Posterior, with an average gain asymmetry of 5.87%. One sample T-test were conducted to compare Lateral responses to a previous study by Mossman et al. (2015) where significant differences in velocity gain at 60 ms and 80 ms between studies were found where, t (59) = 5.56, p <0.01 and t (59) = 2.86, p < 0.01 respectively. Conclusion: This indicates the importance of establishing on-site norms for every clinical settings as techniques used and equipment differences could affect the results.